Legal Politics Of Digitalization Policy In The Implementation Of General Elections In The Context Of Prevention Of General Election Disputes In Indonesia (Journal of Namibian Studies : History Politics Culture, 2023)
The research aims to examine and explain the Political Law of Digitalization Policy in the implementation of general elections in the context of preventing General Election disputes in Indonesia. General elections in Indonesia have undergone a significant transformation with the adoption of information technology and digitalization in the implementation process. In this context, the legal politics of digitalization policy is crucial to prevent and overcome potential disputes in general elections. This study aims to investigate the role of digitalization policy in efforts to prevent election disputes in Indonesia. The problem to be discussed in this study is how urgent is the Digitalization Policy in the implementation of general elections in the context of preventing General Election disputes in Indonesia. The research method used is a normative research method with a statute approach and analyzed using content analysis